Comparison of Metabolic Risk Factors in Urolithiasis Patients according to Family History - Park, Cheol (The Korean Urological Association, 2010)
PURPOSE: Urolithiasis develops more frequently in patients with a family history (FHx). However, little is known about risk factors in stone formers with a FHx. The aim of this study was to examine the clinico-metabolic characteristics of urinary stone formers according to FHx. MATERIALS AND METHODS: A database of 1,068 stone formers who underwent a complete metabolic evaluation was reviewed. The patients were divided into two groups on the basis of the presence of a FHx. Clinical factors and metabolic parameters were compared between the two groups. RESULTS: There were no significant differences in clinical characteristics, such as gender, age, body mass index, stone episodes, or multiple stones, between the two groups (p>0.05, respectively). Compared with stone formers without a FHx, however, serum calcium concentrations were more elevated in stone formers with a FHx. Also, the urinary excretion of calcium was higher in stone formers with a FHx than in those without a FHx. Other urinary metabolites showed no significant differences between the two groups (p>0.05, respectively). CONCLUSIONS: Our study revealed that stone formers with a FHx had increased urinary calcium excretion as well as elevated concentrations of serum calcium. This finding suggests that urolithiasis in stone formers with a FHx may be associated with calcium metabolic abnormalities.